Comparison of Pelvic Floor Muscle Function in Women With Stress Urinary Incontinence and Overactive Bladder and Healthy Women - Delara Kasaeian; Farideh Dehghan Manshadi; Nasim Shokouhi; Elahe Miri; Seyed Mehdi Tabatabaee (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims Urinary incontinence (UI) has been known as one of the clinical manifestations of pelvic floor muscle (PFM) instability; however, limited research has been published on PFM function in patients with different types of UI. This study aimed to compare the PFM function of the continent women and women with Stress urinary incontinence (SUI) and overactive bladder (OAB). Methods This cross-sectional comparative study was performed on 30 women, 10 continents, 10 SUI, and 10 OAB, with a mean age of 42.67±4.77 years. PFM function was assessed using manual muscle testing, a perimeter, and surface electromyography. Data analysis was performed using SPSS software and the level of significance was considered as P≥0. 05. Results There was no significant difference in the PFM function, strength, and electromyographic activity between SUI and OAB patients. However, it decreased in both groups compared to the healthy group (P=0.001). Also, a strong correlation was found between clinical examination, a perimeter, and electromyography (r=0.82, P=0.0001). Conclusion This study revealed that the PFM function was impaired in both groups of women with SUI and OAB. Also, both manual examination and the perimeter can be used as clinical methods in evaluating PFM function.